(untitled) (Research, Society and Development, 2021)
Objective: To analyze whether the indications for cesarean section performed in a low risk reference maternity in Sergipe are in accordance with the Ministry of Health guideline published in 2016. Methods: Documentary, prospective, qualitative, descriptive and cross-sectional study, with data collection through analysis of 318 post-cesarean section medical records from 2018 to 2019. The data obtained were analyzed using descriptive statistics with the aid of the Graph Pad Prism and SPSS 20 software. The study was approved by the Research Ethics Committee. Results: The main indication found was a previous cesarean section, followed by others such as: cephalopelvic disproportion, breech presentation, iterativity, fetal distress, macrosomia, induction failure and post-datism. Conclusion: According to the main indication found, the indications are not fully in accordance with the guideline. However, other indications found are correct, but are outside the guideline because they are situations of intra-delivery care and urgency, not discussed in the document.